FUNGSI DAN DISTRIBUSI FRASA PREPOSISIONAL DALAM BAHASA BUGIS DIALEK SAWITTO - Muh. Asri B. (Balai Bahasa Sulawesi Tengah, 2013)
Prepositional phrase is one of phrases which has its own uniqueness. The uniqueness is on its function which could not become subject, predicate, and object, but it only become one of gramatical function in clause, that is adverb function. The function and distribution will be described in thispaper. The field study and library study is applied. The aim is to describe the function and distribution of prepositional phrase in Sawitto Dialect of Bugis Language in a unit of syntax. The analysis is shown that the prepositional phrase becomes the adverb function such as 1) adverb of time; 2) adverb of place; 3)adverb of aim; 4) adverb of complement; 5) adverb of similative; and 6)adverb of causative. In the distributional function, the prepositional phrase becomes in all position in sentence, whether in the beginning, middle, and ending position.